THE ANALYSIS OF SEMIOTICS IN “THE MAIN CHARACTER OF RAYA AND THE LAST DRAGON FILM” - Karta Atmaja (LINGUA : JURNAL ILMIAH, 2021)
This research is aimed to find the signs then interpret the meaning of signs in Raya and the last dragon film. This film is the first Walt Disney project that was inspired by Southeast Asian cultures especially Indonesia. The design of the study is a semiotics approach by using Charles Sander Peirce’s theory. The type of research is a descriptive qualitative research method. The signs are collected, reduced, classified with Object Triadic; Icon, Index and Symbol then find the Interpretant through correlation between Representamen and Object. There are 30 signs found in the research. The meaning of the sign is divided into two categories, namely the meaning is appropriate with the story and the rest have representation about cultures. From the research of this film we can conclude a moral value: trust and togetherness and also pride about Southeast Asian cultures especially Indonesia can be shown abroad.